(untitled) (International Seven Journal of Multidisciplinary, 2024)
The present work aimed to analyze the circular economy applied to civil construction, highlighting the main theoretical foundations, the challenges faced in Brazil and the opportunities that can boost the sustainable development of the sector. To this end, an integrative literature review was carried out, including scientific articles, technical reports and normative documents published in the last ten years, with an emphasis on studies that addressed waste reuse practices, design for disassembly and sustainable management of materials. The qualitative methodology allowed the content to be organized into thematic categories that included the central concepts of the circular economy, the economic, technological, and cultural barriers that hinder its large-scale adoption, and the strategies that can contribute to consolidating more efficient production models aligned with environmental commitments. Among the main results, it was found that the absence of adequate infrastructure, the lack of specific regulations and the low level of awareness of the consumer market remain limiting factors. On the other hand, it was found that specific successful experiences, especially in large urban centers, demonstrate the potential for reducing environmental impacts and generating economic value associated with circularity. The study reinforces the need for public policies that combine financial incentives, clear technical standards and professional training actions, in addition to highlighting the importance of an articulated national strategy that establishes goals and performance indicators. It is concluded that the circular economy represents a concrete opportunity to transform the Brazilian civil construction towards more responsible and innovative practices, provided that the structural limitations that still restrict its advancement are overcome.